MERETAS SISTEM PEMBELAJARAN PARADIGMA BARU - Pujiriyanto, Pujiriyanto (MAJALAH ILMIAH PEMBELAJARAN, 2011)
New educational paradigm is strongly needed for education reform in Indonesia. Educational system is influenced by the social system at macro, mezzo, and micro level as consequence education system must be respective and pro active to response the social system changes. The concepts of workplace, family, and society are change systematically. Industrial age is going to shif to information age society with different characteristic. There are two important aspects management and learning method. Education management should be more open to network for knowledge sharing. The learning methods should be change in order make the learner as the subject of knowledge construction and be active participant in learning process. The school as education institution should develop partnership and network with others education institution.